Relationship between IGF2a intron 3 single nucleotide polymorphisms and growth performance of Cyprinus carpio - Su Shengyan; Dong Zaijie; Zhu Wenbin; Yuan Xinhua (浙江大学学报. 农业与生命科学版)
Carp production occupies important status in our country. As a new improved variety, FFRC strain carp (Cyprinus carpio) grows faster and has stronger resistance than other varieties of carp. Insulin-like growth factor 2 (IGF2) plays the role of a middle messenger for the growth hormone by single nucleotide polymorphism and expression variation. It has been expressed in a variety of species as well as in the carp. Two distinct genes encoding IGF2 peptides (IGF-2a, and IGF-2b) from common carp have been cloned and identified. This article investigated the carp IGF2a single nucleotide polymorphism (SNP) and growth traits correlation between FFRC strain carp, intron 3 SNP of IGF2a gene about C. carpio var. FFRC strain carp as experimental materials. When they were grown up to 10 g, all fish were tagged by passive integrated transponder (PIT) approach. Then the same environment was created to rear such fish for five months using commercial feed.A total of 32 carp were selected randomly and measured to have the growth performance records from the concrete tanks in Yixing, which are affiliated to the Freshwater Fisheries Research Center, Chinese Academy of Fishery Sciences. These fish were slaughtered and immediately dissected to collect 50-100 mg breast muscle. After the DNA extraction and PCR amplification, using TaKaRa kits, the SNP and the relationships between such locus and C. carpio var. FFRC strain carp were analyzed by sequence and bioinformatics’ software. The relationships between SNP detected and FFRC strain carp growth traits were also analyzed by SAS 8.0.In the present study, DNA sequence (468 bp) of common carp IGF2a intron 3 was isolated and 4 SNPs in common carp IGF2a were found and named by their location. Of them, heterozygous A/G genotype located 256-257 could reduce the body mass and body length of FFRC strain carp; nevertheless, the mass reduction rate is higher than the body length, however both body mass and body length reduction was not significant. The body length and body mass ratio for heterozygous A/G genotype and homozygous G/G genotype had remarkable difference; meanwhile, the heterozygote makes the correlation coefficient of body length and body mass increase. The result also showed that female's body mass, body length and the ratio of body mass to body length were higher than males for G/G genotype, but the ratio of body length to body mass was larger, and the absolute values of body mass and body length were smaller and the ratio of body length to body mass had significant difference between the male and female fish.Generally, the above results suggest that the IGF2a intron 3 polymorphism can influence the body mass and body length of FFRC strain carp. Moreover, heterozygous A/G genotype located 256-257 may be related to visceral mass gain owing to the remarkable effect on body mass and body length ratio. Furthermore, such locus can make interaction with gender by influencing the growth performance of carp. These results will provide information for molecular assisted breeding by increasing the IGF2a heterozygote percentage of the whole population.